2018
DOI: 10.3390/jimaging4070091
|View full text |Cite
|
Sign up to set email alerts
|

Faster R-CNN-Based Glomerular Detection in Multistained Human Whole Slide Images

Abstract: The detection of objects of interest in high-resolution digital pathological images is a key part of diagnosis and is a labor-intensive task for pathologists. In this paper, we describe a Faster R-CNN-based approach for the detection of glomeruli in multistained whole slide images (WSIs) of human renal tissue sections. Faster R-CNN is a state-of-the-art general object detection method based on a convolutional neural network, which simultaneously proposes object bounds and objectness scores at each point in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 34 publications
2
43
0
3
Order By: Relevance
“…In the realm of digital pathology, several recent studies have proposed CAD systems for glomerulus identification and classification in renal biopsies [1][2][3][4][5][6][7][8]. The eligibility for transplantation of a kidney retrieved from Expanded Criteria Donors (ECD) relies on rush histological examination of the organ to evaluate suitability for transplant [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the realm of digital pathology, several recent studies have proposed CAD systems for glomerulus identification and classification in renal biopsies [1][2][3][4][5][6][7][8]. The eligibility for transplantation of a kidney retrieved from Expanded Criteria Donors (ECD) relies on rush histological examination of the organ to evaluate suitability for transplant [9].…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that the CNN method outperformed the HOG and SVM classifier [1]. Kawazoe et al faced the task of glomeruli detection in multistained human kidney biopsy slides by using a Deep Learning approach based on Faster R-CNN [6]. Marsh et al developed a deep learning model that recognizes and classifies sclerotic and non-sclerotic glomeruli in whole-slide images of frozen donor kidney biopsies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pre-processing and the amount of training data will strongly affect detection accuracy for automatic glomerular analysis, most literature about glomerulus classification and detection mention little about these problems. For example, Kawazoe et al [14] proposed a method of using Faster R-CNN to detect glomeruli on periodic acid-Schiff (PAS), periodic acidmethenamine silver (PAM), Masson trichrome (MT) and Azan stained renal WSIs. In their methods, images are taken by 40× objective lens magnification and detection is conducted with downsampling equivalent to 5× objective lens magnification.…”
Section: A Renal Wsi Pre-processing and Analysismentioning
confidence: 99%
“…Quite recently, evidence of a faster lesion detection approach is being reported due to advances in algorithms and metastasis learning in glomerular lesion and gastric cancer detection. 20,21 This study aimed to construct and evaluate an AI model for SLPC detection by using a highly efficient learning system.…”
Section: Introductionmentioning
confidence: 99%